Harnessing Performance Management to Elevate Lecturer Effectiveness in Nigerian Colleges - Saheed Oyeniran; Yusuf Maryam Adedolapo; Yusuf Habibat Abubakar; Taibat Bolanle Jimoh (Indonesian Journal of Education and Social Studies, 2024)
The role of lecturers is vital in achieving the objectives of colleges of education, necessitating their optimal performance. This study examines the connection between performance management practices such as competency, culture, leadership, measurement and reward-based and lecturer effectiveness in colleges of education in southwest Nigeria. A correlational survey research design to explore relationships between variables and predict outcomes, the study utilized multistage sampling techniques to select regional colleges, including stratified, purposive, and proportionate methods. This sampling method was used due to the large and geographically dispersed population involving different schools. Out of a targeted population of 583, 459 participants were included. Data were gathered using the Performance Management Questionnaire (PMQ) and the Lecturers' Effectiveness Questionnaire (LEQ). The instruments were validated using the ordinal alpha reliability technique, yielding the ordinal alpha reliability coefficient of 0.95 and 0.90 for PMQ and LEQ, respectively. Four research questions were addressed using median descriptive statistics, while one central and four operational hypotheses were tested using the Partial Least Square Structural Equation Model (PLS-SEM). The study revealed that performance management levels are very high in these colleges, and lecturer effectiveness is encouraging. A notable relationship exists between career-based and culture-based performance management and lecturer effectiveness. The study recommends that administrators and managers of colleges of education enhance current performance management practices through policy development and establish a framework to address concerns about the quality of teachers graduating from these institutions.